2019
DOI: 10.1016/j.envpol.2019.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Are the primary characteristics of polystyrene nanoplastics responsible for toxicity and ad/absorption in the marine diatom Phaeodactylum tricornutum?

Abstract: Nowadays, the occurrence of a large volume of plastic litter in oceanic and coastal zones has increased concern about its impacts on marine organisms. The degradation of plastic polymers leads to the formation of smaller fragments at both micro and nano scale (<5 mm and <1 µm respectively). Nanoplastics (NPs), due to their smaller size and high specific surface area can establish colloidal interactions with marine microalgae, therefore potential toxicity can be led. . To assess this hypothesis, the aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(66 citation statements)
references
References 61 publications
(68 reference statements)
2
62
1
1
Order By: Relevance
“…Interestingly, most of the studies reported no or limited effect on microalgal growth after exposure to increasing concentrations of plain PS and PS-COOH NPs (Bergami et al, 2017;Yi et al, 2019) up to 250 µg ml −1 (Sjollema et al, 2016), while many sub-lethal physiological alterations have been observed, such as a strong adsorption of nanoplastic agglomerates on microalgal surface (Bergami et al, 2017;Sendra et al, 2019b;Yi et al, 2019), a decrease in photosynthesis efficiency and lipid content, as well as the production of reactive oxygen species (ROS) (González-Fernández et al, 2019;Sendra et al, 2019b;Seoane et al, 2019). Moreover, a significant increase in the DNA damage as well as depolarization of mitochondrial and cell membrane were found in the benthic diatom Phaeodactylum tricornutum exposed to increasing concentrations (in the range 0.1-50 µg ml −1 ) of plain PS NPs, although toxicity was not affected by their nominal sizes of 50 and 100 nm (Sendra et al, 2019b). Recent findings also underline how PS-COOH (50 nm) adhesion onto a diatom's surface causes a reduction in their chain length with potential ecological implications as, for instance, changes in diatom's chain buoyancy as well as the formation and sinking of aggregates (Bellingeri et al, 2020).…”
Section: Effects On Marine Organismsmentioning
confidence: 99%
“…Interestingly, most of the studies reported no or limited effect on microalgal growth after exposure to increasing concentrations of plain PS and PS-COOH NPs (Bergami et al, 2017;Yi et al, 2019) up to 250 µg ml −1 (Sjollema et al, 2016), while many sub-lethal physiological alterations have been observed, such as a strong adsorption of nanoplastic agglomerates on microalgal surface (Bergami et al, 2017;Sendra et al, 2019b;Yi et al, 2019), a decrease in photosynthesis efficiency and lipid content, as well as the production of reactive oxygen species (ROS) (González-Fernández et al, 2019;Sendra et al, 2019b;Seoane et al, 2019). Moreover, a significant increase in the DNA damage as well as depolarization of mitochondrial and cell membrane were found in the benthic diatom Phaeodactylum tricornutum exposed to increasing concentrations (in the range 0.1-50 µg ml −1 ) of plain PS NPs, although toxicity was not affected by their nominal sizes of 50 and 100 nm (Sendra et al, 2019b). Recent findings also underline how PS-COOH (50 nm) adhesion onto a diatom's surface causes a reduction in their chain length with potential ecological implications as, for instance, changes in diatom's chain buoyancy as well as the formation and sinking of aggregates (Bellingeri et al, 2020).…”
Section: Effects On Marine Organismsmentioning
confidence: 99%
“…Furthermore, the finding that species such as G. duebeni can also produce numbers of nanoplastics suggests a new pathway for the environmental presence of nanosized plastics, which are of high concern as they can potentially pass through cell wall barriers and produce adverse effects. Adverse effects of nanoplastics have already been reported in microalgae [60][61][62] , aquatic 63 and terrestrial 64,65 plants, daphnids 60,66 or blue mussel larvae 67 . Moreover, the findings presented here can also be highly relevant for plastic modelling studies as biological fragmentation is currently not considered in the fate of plastics in the environment 68 .…”
Section: Discussionmentioning
confidence: 97%
“…The results of the present study are therefore in contradiction to the expectation that nanoplastics are more hazardous than microplastics (Lehner et al 2019). Indeed, some studies have shown that smaller sized nanoplastics exhibited higher toxicity than larger particles (Fadare et al 2019; Li et al 2020), yet some other studies have also shown no size‐dependent effect or even shown that larger particles were more toxic (Sendra et al 2019; Choi et al 2020). To further understand the effect of size on nanoplastic ecotoxicity, we conducted a statistical analysis based on 21 ecotoxicity data for D. magna and found no statistically significant effect of size on ecotoxicity of nanoplastics for the mass‐based NOECs.…”
Section: Discussionmentioning
confidence: 99%